(untitled) (CIPEEX, 2025)
Introduction: Primary Health Care (PHC) in Brazil is responsible for the initial care of the population, based on health promotion and education. However, the high patient demand that is associated with limited resources contributes to the workload of nursing technicians, which has a detrimental effect on their physical and mental well-being. Objective: of this study is to undertake a comprehensive review of the extant literature concerning factors related to workload and its impact on the mental health of PHC nursing technicians. Methodology: This integrative review was conducted in the Virtual Health Library (VHL), the Publisher Medline (PubMed), and the Scientific Electronic Library Online (Scielo). The search employed a combination of Boolean operators, employing the following descriptors: health professionals, mental health, primary health care, and nurses or nursing technicians. The corpus of articles was limited to those published in Portuguese or English, and to articles published in the last five years. Initially, 392 articles were identified; However, following a screening process that involved title and abstract, only five articles remained for final analysis. Results: Of the five selected studies, four indicated a high prevalence of emotional distress among PHC nursing technicians, particularly women over 60, married, and with children. The impact of the pandemic was further exacerbated by an increased utilization of psychotropic medications. Conclusion: It is imperative that PHC units acknowledge the significance of psychological support within the workplace. To this end, organizational strategies aimed at redistributing tasks, strengthening multidisciplinary support, improving infrastructure, and implementing more equitable management processes must be adopted.